Negative electrode paste, negative electrode comprising same, and lithium secondary battery
By using single-wall carbon nanotube predispersion liquid and organic-based adhesive in the negative electrode slurry, the problem of volume expansion and conduction path blocking of silicon-based compounds in lithium secondary batteries is solved, and higher cycling characteristics are achieved and energy density.
Patent Information
- Application Number
- CN202380049716.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-12-08
- Publication Date
- 2025-02-07
AI Technical Summary
When a silicon-based compound is used as the negative electrode active material, it is prone to oxidation reaction with water to generate hydrogen, resulting in volume expansion, blocking the conductive path, and thus causing deterioration of the characteristics of lithium secondary batteries.
A predispersion containing single-walled carbon nanotubes predispersed in N-methyl-2-pyrrolidone is used as a conductive material, and an organic-based adhesive is used to maintain the carbon nanotube structure to prevent hydrogen generation and conductive path blocking.
By reducing the amount of hydrogen generated during manufacturing and storage, maintaining the conductive path, improving phase stability, the cycle characteristics and energy density per unit volume of lithium secondary batteries are significantly improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application claims the priority and benefits of Korean Patent Application No. 10-2022-0183268, filed with the Korean Intellectual Property Office on December 23, 2022, the entire content of which is incorporated herein by reference.
[0002] The present invention relates to a negative electrode slurry, a negative electrode including the same, and a lithium secondary battery. Background Art
[0003] Due to the rapid increase in the use of fossil fuels, the demand for using alternative or clean energy sources is increasing day by day. As part of this trend, the most actively studied fields are power generation and power storage fields using electrochemical reactions.
[0004] Currently, representative examples of electrochemical devices using such electrochemical energy include secondary batteries, and their usage range is getting wider and wider.
[0005] On the other hand, with the technological development and increasing demand for mobile devices, the demand for secondary batteries has also increased rapidly. Therefore, lithium secondary batteries having characteristics such as high energy density and voltage, long cycle life, and low self-discharge rate have been commercialized and widely used. Therefore, as electrodes for high-capacity lithium secondary batteries, research has been actively carried out to manufacture electrodes with high energy density per unit volume.
[0006] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. In particular, the negative electrode includes a negative electrode active material, and silicon-based particles with a large charge-discharge capacity can be used as the negative electrode active material.
[0007] In particular, recently, in order to meet the demand for secondary batteries with high-energy electrodes, active research has been carried out on methods to increase the capacity by using silicon-based compounds such as Si / C or SiOx (0 < x < 2), which have a capacity 10 times higher than that of graphite-based materials, as negative electrode active materials. However, compared with existing graphite-based materials, the problem with silicon-based compounds is that when stored in a slurry state, hydrogen gas is generated due to an oxidation reaction with water, and volume expansion occurs during charge and discharge, thereby blocking the conduction path, resulting in deterioration of battery characteristics.
[0008] To solve the above problems, research has also been carried out on the composition of adhesives. As a result, adhesive polymers with strong stress have been studied. However, these adhesive polymers themselves have limitations in preventing an increase in electrode thickness due to the shrinkage and expansion of the negative electrode active material and the resulting deterioration of the performance of lithium secondary batteries derived therefrom. In addition, to solve the above problems caused by the volume expansion of the negative electrode with a silicon-based active material, a water-based adhesive with high dispersibility is used.
[0009] In addition, in order to ensure the conductivity of the negative electrode, the secondary battery also includes a conductive material. Although carbon black and the like are mainly used in the related art, in order to improve the capacity of the secondary battery, single-walled carbon nanotubes (SWCNT) with a thin and elongated shape are used. Typically, a dispersion in which single-walled carbon nanotubes are completely dispersed is used to make a negative electrode slurry, and the negative electrode slurry is used to make a negative electrode active material layer. However, when the single-walled carbon nanotubes are completely dispersed, there is a problem that the carbon nanotube structure may not be easily formed. Recently, a method for alleviating the problem has been mentioned, in which the single-walled carbon nanotubes are pre-dispersed at a certain level in a dispersion medium so that most of the single-walled carbon nanotubes exist in a carbon nanotube structure.
[0010] However, when single-walled carbon nanotubes are pre-dispersed at a certain level in a dispersion medium, there is a problem that the carbon nanotube structure cannot be maintained in an aqueous system including an aqueous binder.
[0011] Therefore, various methods have been discussed to solve the above-mentioned problems, and as one of the methods, research on negative electrode binders has been discussed. Summary of the invention
[0012] Technical issues
[0013] The present inventors have found that the above-mentioned problems can be solved by implementing a negative electrode slurry in which a silicon-based active material with a large charge and discharge capacity is used as the negative electrode active material, a pre-dispersion liquid in which single-walled carbon nanotubes are pre-dispersed in a dispersion medium is used as the conductive material, and an organic-based binder is used so that the carbon nanotube structure achieved by the pre-dispersion liquid can be maintained.
[0014] Furthermore, the present inventors have confirmed that by using N-methyl-2-pyrrolidone (NMP) as a dispersion medium, the carbon nanotube structure is more easily maintained and the phase stability with the binder is improved.
[0015] Therefore, the present invention aims to provide a negative electrode slurry comprising the above technical features, a negative electrode comprising the negative electrode slurry, and a lithium secondary battery.
[0016] Technical Solution
[0017] An exemplary embodiment of the present specification provides a negative electrode slurry, the negative electrode slurry comprising: a negative electrode active material; single-walled carbon nanotubes (SWCNT); an organic-based binder; and an organic solvent, wherein the negative electrode slurry comprises a pre-dispersion liquid in which the single-walled carbon nanotubes are dispersed in N-methyl-2-pyrrolidone (NMP).
[0018] In addition, an exemplary embodiment of the present specification provides a negative electrode including: a negative electrode collector layer; and a negative electrode active material layer provided on one surface or both surfaces of the collector layer, wherein the negative electrode active material layer includes the negative electrode slurry or a dried product thereof.
[0019] Finally, an exemplary embodiment of the present specification provides a lithium secondary battery including: a first electrode; a second electrode; a separator interposed between the first electrode and the second electrode; and an electrolyte, wherein either the first electrode and the second electrode is the negative electrode.
[0020] Beneficial Effects
[0021] The negative electrode slurry according to the present application uses an organic solvent to prevent hydrogen generation, so as to prevent the oxidation reaction with water in the slurry state containing the silicon compound from generating hydrogen. In addition, since the dispersion stability of SWCNTs dispersed in NMP is excellent compared with SWCNTs dispersed in water, the conductive connectivity of the electrode is excellent, so that the connectivity of the conductive network during charge and discharge is excellent, so that the cycle characteristics are excellent.
[0022] Therefore, the negative electrode slurry according to the present application has a large charge and discharge capacity, generates a small amount of hydrogen during the manufacture and storage of the slurry, can maintain a conductive path by maintaining a carbon nanotube structure during repeated charge and discharge processes, and has excellent phase stability.
[0023] In addition, a negative electrode including the negative electrode slurry has high energy density per unit volume and improved conductivity.
[0024] In addition, a secondary battery including the negative electrode has high energy density and voltage, thereby providing effects of improved capacity, long cycle life, and low self-discharge rate. DETAILED DESCRIPTION
[0025] Before describing the present invention, some terms will first be defined.
[0026] Unless otherwise specifically stated, in the present specification, when a component “comprises” a constituent element, this does not mean excluding another constituent element but means that another constituent element may further be included.
[0027] In this specification, “p to q” means a range of “p or more and q or less”.
[0028] In this specification, "specific surface area" is measured by the BET method, specifically, calculated from the amount of nitrogen adsorbed at liquid nitrogen temperature (77 K) using BELSORP-mini II manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area may mean the specific surface area measured by the measurement method.
[0029] In this specification, "Dn" means particle size distribution, and means the particle size at the n% point according to the cumulative distribution of the number of particles of the particle size. That is, D50 is the particle size (average particle size) at the 50% point according to the cumulative distribution of the number of particles of the particle size, D90 is the particle size at the 90% point according to the cumulative distribution of the number of particles of the particle size, and D10 is the particle size at the 10% point according to the cumulative distribution of the number of particles of the particle size. On the other hand, the average particle size can be measured using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measuring device (e.g., S3500 of Mychik) to measure the difference in the diffraction pattern according to the particle size when the particles pass through the laser beam to calculate the particle size distribution.
[0030] In an exemplary embodiment of the present application, the particle size or particle diameter may mean an average diameter or a representative diameter of each grain forming the metal powder.
[0031] In the present specification, the fact that a polymer contains a monomer as a monomer unit means that the monomer participates in a polymerization reaction and is therefore contained in the polymer as a repeating unit. In the present specification, when a polymer contains a monomer, this is interpreted as being the same as when a polymer contains a monomer as a monomer unit.
[0032] In the present specification, unless otherwise specified as a "homopolymer", "polymer" is understood to be used in a broad sense including copolymers.
[0033] In this specification, weight average molecular weight (Mw) and number average molecular weight (Mn) are polystyrene conversion molecular weights measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise specified, molecular weight means weight average molecular weight.
[0034] Hereinafter, the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.
[0035] <Negative electrode slurry>
[0036] An exemplary embodiment of the present specification provides a negative electrode slurry, the negative electrode slurry comprising: a negative electrode active material; single-walled carbon nanotubes (SWCNT); an organic-based binder; and an organic solvent, wherein the negative electrode slurry comprises a pre-dispersion liquid in which the single-walled carbon nanotubes are dispersed in N-methyl-2-pyrrolidone (NMP).
[0037] Since the negative electrode slurry according to the present application comprises the organic binder and the pre-dispersion liquid containing single-walled carbon nanotubes, the negative electrode slurry has excellent carbon nanotube negative electrode slurry phase stability compared to an aqueous system comprising an aqueous binder, so that the negative electrode slurry has excellent conductive network connectivity during repeated charge and discharge processes, and a small amount of hydrogen is generated during the manufacture and storage of the slurry.
[0038] In the present specification, the organic binder is used to capture the negative electrode active material and / or the conductive material to prevent distortion and structural deformation of the negative electrode structure during volume expansion and relaxation of the negative electrode active material. In addition, compared with aqueous binders, the organic binder has excellent compatibility with single-walled carbon nanotubes, so phase stability can be maintained. In the present specification, the organic binder is a polymer that can be dissolved in an organic solvent, and there is no particular limitation as long as it satisfies the role of an organic binder.
[0039] In the present specification, the mixing method for forming the negative electrode slurry is not particularly limited, and examples thereof include a ball mill, a sand mill, a pigment disperser, an ultrasonic disperser, a homogenizer, a planetary mixer, a Hobart mixer, etc., and kneading is preferably performed using a homogenizer and / or a planetary mixer, as the case may be.
[0040] In an exemplary embodiment of the present invention, the negative electrode active material may include one or more selected from the group consisting of silicon-based active materials and carbon-based active materials.
[0041] In an exemplary embodiment of the present specification, the electrode active material may be composed of a mixture of a silicon-based active material and a carbon-based active material.
[0042] In this specification, the capacity of the silicon-based active material is 10 times that of the carbon-based active material. Therefore, when the silicon-based active material is applied to an electrode, especially a negative electrode, an electrode with a higher energy density level can be achieved even if the thickness is thinner than when it only contains the carbon-based active material.
[0043] In another exemplary embodiment of the present specification, when the electrode active material is composed of a silicon-based active material and a carbon-based active material, a composition ratio between the silicon-based active material and the carbon-based active material may be in a range of 2:98 to 30:70.
[0044] The electrode active material according to the exemplary embodiment contains a carbon-based active material as a main component, and thus the following effects can also be provided. Since the active material has a small volume expansion during charge and discharge, the swelling that occurs is slight, and the conductive connectivity of the electrode is excellent.
[0045] In an exemplary embodiment of the present specification, the silicon-based active material may include one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloy.
[0046] In the present specification, the electrode active material contains silicon particles that can exist, for example, in crystalline or amorphous form. Specifically, the silicon particles may preferably be spherical particles, but are not limited thereto.
[0047] In the present specification, the case of SiO2 where x is 2 in SiOx is not included. This SiO2 does not react with lithium ions and thus cannot store lithium. Therefore, it is preferred that x falls within the range of the exemplary embodiment.
[0048] In the present specification, the silicon-based active material may be Si / C composed of a composite of Si and C, or Si.
[0049] In the present specification, two or more of the silicon-based active materials may be used as a mixture.
[0050] In an exemplary embodiment of the present specification, the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, it may include 70 parts by weight or more of SiOx (x = 0).
[0051] In the negative electrode paste, when the content of the silicon-based active material satisfies the above range, the binder and the conductive material can be effectively combined with the silicon active material, and the conductive connectivity between the active materials can be smoothly maintained.
[0052] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the content of SiOx (x = 0) may be 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and its content may be 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.
[0053] In an exemplary embodiment of the present specification, for the silicon-based active material, in particular, pure silicon (Si) can be used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean that, based on a total of 100 parts by weight of the silicon-based active material, pure Si particles (SiOx (x=0)) within the above range that are not combined with other particles or elements are included.
[0054] Since the capacity of the silicon-based active material is very high compared with the graphite-based active material used in the related field, attempts to apply the silicon-based active material are increasing, but since the volume expansion rate of the silicon-based active material is large during repeated charge and discharge processes, the attempts are limited to cases where a small amount of the silicon-based active material is mixed with the graphite-based active material and used.
[0055] Therefore, the present invention solves the existing problems by preparing a negative electrode pre-dispersion liquid to improve the dispersibility of carbon nanotubes, enhancing the combination with the active material to solve the above problems, and using only the silicon-based active material as the negative electrode active material to improve the capacity.
[0056] On the other hand, the average particle size (D50) of the silicon-based active material of the present invention can be 3 μm to 10 μm, specifically 3.5 μm to 8 μm, and more specifically 3.5 μm to 7 μm. When the average particle size is included in the above range, since the specific surface area of the particles is included in a suitable range, the viscosity of the negative electrode slurry formed is within a suitable range. Therefore, the dispersion of the particles constituting the negative electrode slurry is promoted. In addition, the size value of the silicon-based active material is equal to or greater than the lower limit value range, and since the composite composed of the conductive material and the negative electrode binder in the negative electrode slurry makes the contact area between the silicon particles and the conductive material excellent, the possibility of maintaining the conductive network is increased, so that the capacity retention rate is increased. On the other hand, when the average particle size satisfies the above range, the excessively large silicon particles are eliminated, thereby forming a smooth surface of the negative electrode, and therefore, the phenomenon of uneven current density during charge and discharge can be prevented.
[0057] In an exemplary embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably 0.01 to 150.0 m 2 / g, more preferably 0.1 to 100.0 m 2 / g, particularly preferably 0.2 to 80.0 m 2 / g, most preferably 0.2 to 18.0 m 2 The BET specific surface area is measured according to DIN 66131 (using nitrogen gas).
[0058] In an exemplary embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure or be present in the form of a film or coating containing silicon.
[0059] In an exemplary embodiment of the present specification, the carbon-based active material may include one or more selected from the group consisting of artificial graphite, natural graphite, hard carbon, and soft carbon.
[0060] In this specification, the negative electrode composition in the negative electrode slurry means the negative electrode active material, the conductive material and the organic binder excluding the (organic) solvent, and may be referred to as the solid matter of the negative electrode slurry in some cases.
[0061] In an exemplary embodiment of the present application, the following negative electrode composition is provided, in which the content of the silicon-based active material is 60 parts by weight or more based on 100 parts by weight of the solid content of the negative electrode slurry.
[0062] In another exemplary embodiment, the content of the silicon-based active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, based on 100 parts by weight of the solid content of the negative electrode slurry, and its content may be 95 parts by weight or less, preferably 90 parts by weight or less.
[0063] The negative electrode slurry according to the present application has the following characteristics, wherein even if a silicon-based active material with a very high capacity is used within the above range, by using a specific conductive material and a specific negative electrode binder capable of improving the volume expansion rate in repeated charge and discharge processes, the performance of the negative electrode will not deteriorate even within the above range, and the output characteristics during charge and discharge are excellent.
[0064] In an exemplary embodiment of the present application, the silicon-based active material may have a non-circular form, and the circularity thereof is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, or for example, 0.85 to 0.9.
[0065] In the present application, the circularity is determined by the following Formula 1, where A is the area and P is the boundary line.
[0066] [Formula 1]
[0067] 4πA / P 2
[0068] In an exemplary embodiment of the present specification, the pre-dispersion liquid may include 0.4 parts by weight or more of the single-walled carbon nanotube relative to 100 parts by weight of N-methyl-2-pyrrolidone (NMP).
[0069] In an exemplary embodiment of the present specification, the pre-dispersion liquid may include 1 part by weight or more of the single-walled carbon nanotube relative to 100 parts by weight of N-methyl-2-pyrrolidone (NMP).
[0070] In the present specification, the pre-dispersion liquid may further include a dispersant. The dispersant enables the single-walled carbon nanotubes to be smoothly mixed with a dispersion medium such as NMP during the preparation of a conductive mixture such as the pre-dispersion liquid, and can improve the dispersibility of the carbon nanotubes in the conductive material dispersion liquid prepared using the conductive mixture.
[0071] In another exemplary embodiment of the present invention, the dispersant may include at least one selected from the group consisting of hydrogenated nitrile rubber (H-NBR), polyvinyl pyrrolidone (PVP), polyvinylidene fluoride (PVdF) and polyvinyl butyral (PVB). Specifically, the dispersant may be hydrogenated nitrile rubber or PVdF.
[0072] In another exemplary embodiment of the present invention, the content of the dispersant may be 10 wt % or more and 500 wt % or less, specifically, 20 wt % or more or 50 wt % or more, or 300 wt % or less or 200 wt % or less, based on the weight of the single-walled carbon nanotubes. When the above range is met, the single-walled carbon nanotubes can be smoothly dispersed in NMP.
[0073] The single-walled carbon nanotube may be a bundle-type carbon nanotube. The bundle-type carbon nanotube may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" used herein refers to a secondary shape in the form of a bundle or rope in which a plurality of carbon nanotube units are aligned side by side in an alignment in which the longitudinal axes of the carbon nanotube units are substantially the same or entangled. In the single-walled carbon nanotube unit, the graphene sheet has a cylindrical shape with a diameter of nanometer size and has a sp 2 In this case, the carbon nanotube unit may exhibit the characteristics of a conductor or a semiconductor depending on the structure and the rolling angle of the graphite sheet. Compared with the entangled carbon nanotube, the bundle-type carbon nanotube can be evenly dispersed during the manufacture of the negative electrode, and the conductivity of the negative electrode can be improved by smoothly forming a conductive network in the negative electrode.
[0074] Although point-shaped conductive materials, planar conductive materials, and / or linear conductive materials have been used as conductive materials in negative electrode slurries in the related art, currently, thin and elongated linear conductive materials (i.e., single-walled carbon nanotubes) having excellent physical properties in terms of dispersibility are used. In particular, when only the linear conductive material is used, the electrode structure can be improved because the electrode distortion, which is a problem of silicon-based negative electrodes, can be simplified, and therefore, the negative electrode conductive material has the characteristic of being able to reduce the resistance to the movement of lithium ions in the electrode.
[0075] Furthermore, for additional improvement in dispersibility, an amide-based polar organic solvent (particularly NMP) is used as a dispersion medium instead of an aqueous dispersion using distilled water, thereby promoting maintenance of the carbon nanotube structure.
[0076] In addition, when the above range is satisfied, a conductive path of a negative electrode to be manufactured using the negative electrode slurry in the future is ensured, thereby reducing electrode resistance and also improving the service life characteristics of the battery.
[0077] In another exemplary embodiment of the present specification, the content of the single-walled carbon nanotube may be 0.01 parts by weight or more and 1 part by weight or less based on 100 parts by weight of the solid content of the negative electrode slurry.
[0078] In another exemplary embodiment, the content of the single-walled carbon nanotubes may be 0.05 parts by weight or more and 0.8 parts by weight or less, preferably 0.1 parts by weight or more and 0.7 parts by weight or less, and more preferably 0.015 parts by weight or more and 0.5 parts by weight or less, based on 100 parts by weight of the solid content of the negative electrode slurry.
[0079] The negative electrode conductive material according to the present application has a completely different constitution from the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application is used to capture the contact points between the silicon-based active materials in which the volume expansion of the electrode is very large due to charge and discharge, while the positive electrode conductive material is used to impart partial conductivity while playing a buffering role as a mitigation role during rolling, and its constitution and role are completely different from those of the negative electrode conductive material of the present invention.
[0080] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material, and its composition is completely different from that of the conductive material applied to the graphite-based active material. That is, the conductive material used for the electrode having the graphite-based active material has only small particles relative to the active material, and thus has the characteristics of enhancing output characteristics and imparting partial conductivity, and its composition and function are completely different from those of the negative electrode conductive material applied together with the silicon-based active material in the present invention.
[0081] In an exemplary embodiment of the present specification, the organic binder may be one or more selected from the group consisting of polyvinylidene fluoride (PVdF)-based binders, polyamideimide (PAI)-based binders, polyimide (PI)-based binders, polyacrylonitrile (PAN)-based binders, and polyacrylamide (PAM)-based binders.
[0082] In the present specification, the organic binder may be a homopolymer or a copolymer. When the organic binder is a copolymer, the copolymer may be a random copolymer, a block copolymer, an alternating copolymer or a graft copolymer.
[0083] In an exemplary embodiment of the present specification, the organic binder may further include a repeating unit derived from one or more compounds selected from the group consisting of acrylic acid and hexafluoropropylene, or may further include a polyacrylic acid polymer. Examples of the organic binder include PVdF-AA / HFP, PAN-PAA, PAN-PAM, etc., but are not limited thereto.
[0084] In an exemplary embodiment of the present specification, the organic solvent means a non-aqueous organic solvent, and for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.
[0085] In an exemplary embodiment of the present specification, the organic solvent may be N-methyl-2-pyrrolidone (NMP).
[0086] In the present specification, by using the same type of organic solvent and the dispersion medium of the conductive material, an organic system can be secured throughout the negative electrode slurry to help maintain the morphology of the carbon nanotube structure formed in the above dispersion.
[0087] In an exemplary embodiment of the present specification, the weight ratio of the negative electrode active material, the organic binder and the single-walled carbon nanotube can be 70 to 95 (weight %): 3 to 15 (weight %): 0.01 to 1 (weight %). In the present specification, the composition including the negative electrode active material, the organic binder and the single-walled carbon nanotube can be referred to as an electrode composition.
[0088] In an exemplary embodiment of the present specification, the negative electrode slurry may further include an additional conductive material, and the content of the additional conductive material may be 20 wt % or less relative to the total of the negative electrode active material, the organic-based binder, and the single-walled carbon nanotubes.
[0089] In another exemplary embodiment of the present specification, the content of the additional conductive material may be greater than about 0 wt %, greater than about 1 wt %, greater than about 3 wt %, or greater than about 4 wt %, or about 20 wt % or less, about 19 wt % or less, about 18 wt % or less, or about 17 wt % or less, relative to the sum of the negative electrode active material, the organic-based binder, and the single-walled carbon nanotubes (i.e., the electrode composition).
[0090] In the present specification, the additional conductive material is not composed of single-walled carbon nanotubes, and may refer to at least one of a point-like conductive material, a surface-like conductive material, and a line-like conductive material.
[0091] In the present application, the point-shaped conductive material may be preferably used to enhance the conductivity of the negative electrode, and means a point-shaped or spherical conductive material having conductivity without causing chemical changes. Specifically, the point-shaped conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and may preferably contain carbon black in terms of achieving high conductivity and excellent dispersibility.
[0092] In this specification, the planar conductive material can be used to improve conductivity by increasing the surface contact between silicon particles in the electrode, preferably the negative electrode, while suppressing the disconnection of the conductive path due to volume expansion. The planar conductive material can be represented as a plate-like conductive material or a block-like conductive material. Examples of the planar conductive material can include at least one selected from the group consisting of plate-like graphite, graphene, graphene oxide and graphite sheets, and preferably can be plate-like graphite.
[0093] In the present specification, the linear conductive material may be a multi-walled carbon nanotube or a single-walled carbon nanotube.
[0094] In an exemplary embodiment of the present specification, the additional conductive material may be one or more dot-shaped conductive materials. For example, the additional conductive material may be carbon black, artificial graphite, and the like.
[0095] In another exemplary embodiment, the conductive material may be a negative electrode conductive material.
[0096] In this specification, the negative electrode conductive material is applied to the negative electrode and has a completely different configuration from the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material is used to capture the contact points between the silicon-based active materials in which the volume expansion of the electrode is very large due to charge and discharge, and the positive electrode conductive material is used to impart partial conductivity while playing a buffering role as a mitigating role during rolling, so that the structures and functions of the negative electrode conductive material and the positive electrode conductive material are different.
[0097] When the negative electrode slurry according to an exemplary embodiment of the present invention satisfies the above weight ratio, phase stability is improved, and during the manufacture of an electrode, the binder and the conductive material are effectively combined with the negative electrode active material, and conductive connectivity between the active materials can be smoothly maintained.
[0098] In some cases, the type or content of the solvent may be adjusted so that the viscosity of the negative electrode slurry falls within the range of 5000 cps to 6000 cps. Therefore, when one or both surfaces of an electrode collector layer are coated with the negative electrode slurry in the future, coating properties and storage properties are excellent.
[0099] <Negative electrode>
[0100] An exemplary embodiment of the present specification provides a negative electrode, comprising: a negative electrode collector layer; and a negative electrode active material layer provided on one surface or both surfaces of the collector layer, wherein the negative electrode active material layer comprises any one of the above-mentioned negative electrode slurries or a dried product thereof.
[0101] In an exemplary embodiment of the present invention, the solid content of the negative electrode slurry may satisfy 5% to 60%, preferably 5% to 40%.
[0102] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% to 40% both inclusive, preferably 7% to 35% both inclusive, and more preferably 10% to 30% both inclusive.
[0103] The solid content of the negative electrode slurry may mean the content of the negative electrode composition contained in the negative electrode slurry, and may mean the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.
[0104] When the solid content of the negative electrode slurry satisfies the above range, the present invention has the following characteristics: since the viscosity is appropriate during the formation of the negative electrode active material layer, the negative electrode active material layer can be effectively formed by minimizing the aggregation phenomenon of particles of the negative electrode composition.
[0105] In an exemplary embodiment of the present application, as a negative electrode collector layer, the thickness of the collector layer is generally 1 μm to 100 μm. There is no particular limitation on the negative electrode collector layer, as long as the negative electrode collector layer has high conductivity and does not cause chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, a material obtained by surface treatment of the surface of copper or stainless steel with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode collector layer can also increase the bonding strength of the negative electrode active material by forming fine concave-convex on its surface, and the negative electrode collector layer can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0106] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the thickness of the negative electrode collector layer is 1 μm or more and 100 μm or less, and the thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less.
[0107] However, the thickness may be variously modified according to the type and purpose of the negative electrode used, and is not limited thereto.
[0108] In an exemplary embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less.
[0109] In another exemplary embodiment, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.
[0110] The porosity varies depending on the composition and content of the silicon-based active material, the conductive material, and the binder contained in the negative electrode active material layer; in particular, because the silicon-based active material and the conductive material according to the present application are contained in a specific composition and content, satisfying the above-mentioned range, it is characterized in that the conductivity and resistance of the electrode have an appropriate range.
[0111] In an exemplary embodiment of the present application, as a means for providing the negative electrode slurry to the collector layer, a coating device known in the related art, such as a comma coater, a gravure coater, a micro gravure coater, a die coater or a rod coater, may be used, but the means are not limited thereto.
[0112] Thereafter, a drying process may be performed, which may be performed at a temperature of 60° C. to 200° C., or more preferably 100° C. to 180° C., and may be performed in dry air or an inert atmosphere (e.g., argon, etc.), but is not limited thereto. The thickness of the electrode (cured coating film) may be 5 μm to 300 μm, or more preferably 10 μm to 250 μm, but is not limited thereto.
[0113] <Lithium Secondary Battery>
[0114] An exemplary embodiment of the present application provides a lithium secondary battery including: a first electrode; a second electrode; a separator interposed between the first electrode and the second electrode; and an electrolyte, wherein either the first electrode or the second electrode is the negative electrode.
[0115] A secondary battery according to an exemplary embodiment of the present specification may particularly include the above-mentioned negative electrode for a lithium secondary battery. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described in detail, its specific description will be omitted.
[0116] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and containing the positive electrode active material.
[0117] In the positive electrode, there is no particular limitation on the positive electrode collector, as long as the positive electrode collector has conductivity without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or a material in which the surface of aluminum or stainless steel is surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the thickness of the positive electrode collector can generally be 3 to 500 μm, and the adhesion of the positive electrode active material can also be enhanced by forming fine concavoconvexities on the surface of the collector. For example, the positive electrode collector can be used in different forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0118] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material includes: a layered compound, such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or a compound replaced by one or more transition metals; a lithium iron oxide, such as LiFe3O4; a lithium manganese oxide, such as Li 1+c1 Mn 2-c1O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; represented by the chemical formula LiNi 1-c2 M c2 O2 (herein, M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and c2 satisfies 0.01≤c2≤0.3) Ni-site lithium nickel oxide; represented by the chemical formula LiMn 2-c3 M c3 Lithium manganese composite oxides of Li2Mn3MO8 (herein, M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and c3 satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (herein, M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4 in which Li in the chemical formula is partially replaced by alkaline earth metal ions, etc., but are not limited thereto. The positive electrode may be Li metal.
[0119] The positive electrode active material layer may include a positive electrode conductive material and a positive electrode binder as well as the positive electrode active material.
[0120] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the battery to be constituted. Specific examples thereof include: graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof can be used.
[0121] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode current collector. Specific examples thereof may include: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one thereof or a mixture of two or more thereof may be used.
[0122] The separator separates the negative electrode from the positive electrode, provides a channel for the movement of lithium ions, and can be used without particular restriction, as long as the separator is generally used as a separator of a secondary battery, in particular, preferably an electrolyte with excellent moisture retention ability and a small resistance to the movement of ions in the electrolyte. Specifically, a porous polymer film can be used, for example, a porous polymer film formed by a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer and an ethylene / methacrylate copolymer, or a laminated structure of more than two layers thereof. In addition, a typical porous non-woven fabric can also be used, such as a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or multilayer structure.
[0123] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which can be used to manufacture lithium secondary batteries, but are not limited thereto.
[0124] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.
[0125] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate and ethyl propionate can be used.
[0126] In particular, among the carbonate-based organic solvents, cyclic carbonates such as ethylene carbonate and propylene carbonate can be preferably used because they have a high dielectric constant as an organic solvent with high viscosity and therefore dissociate lithium salts well. Moreover, when the cyclic carbonates are mixed with linear carbonates such as dimethyl carbonate and diethyl carbonate having low viscosity and low dielectric constant in an appropriate ratio, an electrolyte with high conductivity can be prepared, so such a combined use is more preferred.
[0127] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily soluble in the non-aqueous electrolyte. For example, as the anion of the lithium salt, a metal salt selected from the group consisting of F - , Cl - ,I- 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - One or more of the groups consisting of.
[0128] In the electrolyte, in order to improve the service life characteristics of the battery, inhibit the decrease in battery capacity and improve the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, one or more additives may be included, for example, halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride.
[0129] The secondary battery according to the present invention can be used in the field of portable devices such as mobile phones, notebook-sized computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs), and can be preferably used as a constituent battery of a medium-to-large battery module. Therefore, the present invention also provides a medium-to-large battery module, which includes the aforementioned lithium secondary battery as a unit cell.
[0130] An exemplary embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and thus can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0131] [Invention Mode]
[0132] In the following, in order to facilitate the understanding of the present invention, preferred embodiments will be proposed, but the embodiments are provided only to illustrate the present invention, and it is obvious to those skilled in the art that various changes and modifications can be made within the scope and technical spirit of the present invention, and such changes and modifications naturally fall within the appended claims.
[0133] Example. Preparation of negative electrode slurry
[0134] <Example 1>
[0135] An electrode composition was prepared in the following manner: Si with d50 = 4.5 μm was used as a negative electrode active material, SWCNTs dispersed in NMP (dispersant: PvdF, weight ratio of SWCNT:PvdF = 1:1) were used as a conductive material, carbon black (Super C65, manufactured by Temeco) and artificial graphite (SFG6L, manufactured by Temeco) were used as additional conductive materials, a polyamideimide (PAI)-based binder was used as a binder, and the resulting mixture was mixed so that Si:C65:SFG6L:SWCNT:the binder = 80:5:5:0.5:10 (by weight ratio).
[0136] The negative electrode slurry was prepared using N-methyl-2-pyrrolidone (NMP) as a solvent, in which case the amount of NMP added was adjusted in consideration of coating properties, viscosity, and solid content. The viscosity of the obtained negative electrode slurry was adjusted to 5000 cps to 6000 cps using a rheometer HR20 (manufactured by TA Instruments).
[0137] <Example 2>
[0138] The negative electrode slurry was prepared in the same manner as in Example 1, except that PAN-PAM (PAN:PAM=95:5 based on the total weight of the binder) was used as the binder.
[0139] <Example 3>
[0140] The negative electrode slurry was prepared in the same manner as in Example 1, except that PAN-PAA (PAN:PAA = 95:5 based on the total weight of the binder) was used as the binder.
[0141] <Example 4>
[0142] A negative electrode slurry was prepared in the same manner as in Example 1, except that artificial graphite:SiC (weight ratio 85:15) was used as the negative electrode active material.
[0143] <Comparative Example 1>
[0144] The negative electrode slurry was prepared in the same manner as in Example 1, except that Na + Instead of PAA as a binder, single-walled carbon nanotubes dispersed in water were used as the conductive material.
[0145] <Comparative Example 2>
[0146] The negative electrode slurry was prepared in the same manner as in Example 1, except that PAM-Na + Instead of PAA as a binder, single-walled carbon nanotubes dispersed in water were used as the conductive material.
[0147] <Comparative Example 3>
[0148] The negative electrode slurry was prepared in the same manner as in Example 1, except that SBR-CMC (SBR:CMC=8:2 based on the total weight of the binder) was used as a binder, and single-walled carbon nanotubes dispersed in water were used as a conductive material.
[0149] <Comparative Example 4>
[0150] The negative electrode slurry was prepared in the same manner as in Example 4, except that Na + Instead of PAA as a binder, water-dispersed single-walled carbon nanotubes were used as the conductive material.
[0151] Experimental example.
[0152] <Experimental Example 1: Measurement of the Amount of H2 Gas Generated in Electrode Slurry>
[0153] 5 g of each of the negative electrode slurries of Examples 1 to 4 and Comparative Examples 1 to 4 were placed in a bag of 9 cm x 9 cm in size, the bag was sealed, and then left to stand in a constant temperature chamber at 60° C. for 24 hours. Next, the gas generated in the bag was captured, and the amount of H2 gas generated was quantitatively analyzed using GC / MS. The results are shown in Table 1 below.
[0154] <Experimental Example 2> Battery Manufacturing and Battery Characteristics Evaluation
[0155] A copper foil having a thickness of 18 μm was coated with each of the negative electrode slurries of Examples 1 to 4 and Comparative Examples 1 to 4 and dried, an active material layer having a thickness of 50 μm was formed on one surface of the copper foil, and the copper foil was punched into a circular shape having a diameter of 14 Φ (mm), thereby manufacturing a test electrode (negative electrode).
[0156] A metal lithium foil with a thickness of 0.3 mm was used as the positive electrode, a porous polyethylene sheet with a thickness of 0.1 mm was used as the separator, and a product obtained by dissolving LiPF6 as a lithium salt with a concentration of about 1 mol / L in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 was used as the electrolyte.
[0157] A coin cell for evaluation having a thickness of 2 mm and a diameter of 32 mm was manufactured by sealing the negative electrode, the positive electrode, the separator, and the electrolyte in a stainless steel container.
[0158] The coin cell was charged at a constant current of 0.05 C until the voltage reached 0.01 V, and then discharged at a constant current of 0.05 C until the voltage reached 1.5 V to determine the discharge capacity and initial efficiency, after which the capacity retention rate test was performed by performing cycle characteristics at a constant current of 0.2 C in the same voltage range as above. The experimental results are shown in Table 1 below.
[0159]
[0160] As shown in Table 1, it can be seen that the batteries manufactured using the negative electrode slurries of Examples 1 to 4 containing the organic binder and single-walled carbon nanotubes (SWCNTs) dispersed in NMP generate less hydrogen and have excellent cycle capacity retention compared to the batteries manufactured using the negative electrode slurries of Comparative Examples 1 to 4.
Claims
1. A negative electrode paste, the negative electrode paste comprising: a negative electrode active material; single-walled carbon nanotubes (SWCNT); an organic binder; and an organic solvent, wherein the negative electrode paste comprises a pre-dispersion in which the single-walled carbon nanotubes are dispersed in N-methyl-2-pyrrolidone (NMP).
2. The negative electrode paste according to claim 1, wherein the negative electrode active material comprises one or more selected from the group consisting of a silicon-based active material and a carbon-based active material.
3. The negative electrode paste according to claim 2, wherein the silicon-based active material comprises one or more selected from the group consisting of SiOx where x = 0, SiOx where 0 < x < 2, SiC, and Si alloys.
4. The negative electrode paste according to claim 2, wherein the carbon-based active material comprises one or more selected from the group consisting of artificial graphite, natural graphite, hard carbon, and soft carbon.
5. The negative electrode paste according to claim 1, wherein the organic binder is one or more selected from the group consisting of a polyvinylidene fluoride (PVdF) binder, a polyamideimide (PAI) binder, a polyimide (PI) binder, a polyacrylonitrile (PAN) binder, and a polyacrylamide (PAM) binder.
6. The negative electrode paste according to claim 5, wherein the organic binder further comprises repeating units derived from one or more compounds selected from the group consisting of acrylic acid and hexafluoropropylene, or further comprises a polyacrylic acid polymer.
7. The negative electrode paste according to claim 1, wherein the organic solvent is N-methyl-2-pyrrolidone (NMP).
8. The negative electrode paste according to claim 1, wherein the weight ratio of the negative electrode active material, the organic binder, and the single-walled carbon nanotubes is 70 to 95 (wt%): 3 to 15 (wt%): 0.01 to 1 (wt%).
9. The negative electrode paste according to claim 1, the negative electrode paste further comprising an additional conductive material, wherein the weight ratio of the additional conductive material is 20 wt% or less relative to the sum of the negative electrode active material, the organic binder, and the single-walled carbon nanotubes.
10. A negative electrode, the negative electrode comprising: a current collector layer; and a negative electrode active material layer provided on one surface or both surfaces of the current collector layer, wherein the negative electrode active material layer comprises the negative electrode paste according to any one of claims 1 to 9 or a dried product thereof.
11. A lithium secondary battery, the lithium secondary battery comprising: a first electrode; a second electrode; a separator interposed between the first electrode and the second electrode; and an electrolyte, wherein either the first electrode or the second electrode is the negative electrode according to claim 10.